2010
DOI: 10.1021/cm100808f
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Graphite Nanoplatelets Formed by Oleum Exfoliation of Graphite

Abstract: A facile route to water-soluble graphite nanoplatelets that uses graphite as the starting material is described. The method relies on the addition of phenyl radicals with subsequent sulfonation of the phenyl groups. Atomic force microscopy, high-resolution transmission electron microscopy, and scanning tunneling microscopy images show that a high degree of exfoliation occurs during the sulfonation step. The sheet resistance of the bulk films of the nanoplatelets prepared by vacuum filtration using an anodisc m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Raman spectra of the initial graphite material and an SGS sample are depicted in Additional file 1: Figure S2. According to previous Raman studies [4], graphene can be identified by monitoring the position of the 2D band, whereby sulfonation of the phenyl groups and subsequent formation of the SGS sodium salt lead to repulsive interactions between the SO 3 − groups (to produce exfoliation), as evidenced by a slight shift in the 2D peak in Additional file 1: Figure S2. Functionalization by sulfonation has also been confirmed by XPS and TGA, which is provided in Additional file 1: Figures S3 and S4, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectra of the initial graphite material and an SGS sample are depicted in Additional file 1: Figure S2. According to previous Raman studies [4], graphene can be identified by monitoring the position of the 2D band, whereby sulfonation of the phenyl groups and subsequent formation of the SGS sodium salt lead to repulsive interactions between the SO 3 − groups (to produce exfoliation), as evidenced by a slight shift in the 2D peak in Additional file 1: Figure S2. Functionalization by sulfonation has also been confirmed by XPS and TGA, which is provided in Additional file 1: Figures S3 and S4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were obtained from Mukherjee et al [4]. In their technique, highly exfoliated SGSs can be synthesized by sulfonation of commercially available graphite (particle size < 20 μm) in oleum to overcome the cohesive van deer Waals attractions between adjacent sheets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, a major impediment that hinders their application in the preparation of the functional materials as well as in biological systems is their inherent insolubility in different organic-aqueous solvents. Covalent chemical functionalization of GNS potentially overcomes these issues by creating functional groups on the surface of the nanosheet, which not only increases its dispersibility in various organic solvents 7,8 but also creates a band gap for applications in photonics and microelectronics. 9 In the case of biological applications, the primary requirement for GNS sample preparation is its dispersibility in water, biocompatibility and nontoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, visibly, important discrepancies emerge. Indeed, some research groups propose that aryl radicals increase conductivity [12,13] whereas others support the opposite behavior. [9][10][11][12][13][14] From a purely chemical standpoint, it has been proposed by some groups that aryl radicals can be attached only at edges [13] whereas others found that the basal plane of graphene is reactive.…”
mentioning
confidence: 99%